2023
DOI: 10.1021/prechem.3c00008
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects of Atomically Precise Gold Nanoclusters in Catalysis

Abstract: The emergence of ligand-protected, atomically precise gold nanoclusters (NCs) in recent years has attracted broad interest in catalysis due to their well-defined atomic structures and intriguing properties. Especially, the precise formulas of NCs provide an opportunity to study the size effects at the atomic level without complications by the polydispersity in conventional nanoparticles that obscures the relationship between the size/structure and properties. Herein, we summarize the catalytic size effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 106 publications
(262 reference statements)
1
17
0
Order By: Relevance
“…), and photochemical reactions (CO 2 reduction, 57,58 dye degradation, 59 etc .). The catalytic activity of medium-sized gold nanoclusters is not solely determined by the size (this has been summarized in recent reviews 60,61 ), but is also related to the surface geometry, electronic properties, and ligand properties of the nanoclusters and cluster–support interaction. Ultimately, the structural evolution of the supported cluster during catalyst pretreatment and reaction creates the actual active sites.…”
Section: Medium Size Nanocluster Precursors (Tens To Hundreds Of Meta...mentioning
confidence: 99%
“…), and photochemical reactions (CO 2 reduction, 57,58 dye degradation, 59 etc .). The catalytic activity of medium-sized gold nanoclusters is not solely determined by the size (this has been summarized in recent reviews 60,61 ), but is also related to the surface geometry, electronic properties, and ligand properties of the nanoclusters and cluster–support interaction. Ultimately, the structural evolution of the supported cluster during catalyst pretreatment and reaction creates the actual active sites.…”
Section: Medium Size Nanocluster Precursors (Tens To Hundreds Of Meta...mentioning
confidence: 99%
“…As shown in table 1, with an increasing number of shedding ligands, the binding strength of O 2 species on the exposed Au atoms of ligand Au NCs are weakened, corresponding to the adsorption energies of −1.14 to −0.56 eV, 0.80 eV to −0. 25 [44][45][46]49]. This is due to the mutual repulsion forces undergone by the filled d orbital electrons in the Au atoms with the antibonding states and the adsorbed states [49,50].…”
Section: Chemical Activities Of Ligand Au Ncs For Co Oxidationmentioning
confidence: 99%
“…The rational synthesis of atomically precise Au NCs has paved the way for gaining fundamental insight into the intrinsic mechanism and establishing the structure-property-application relationship of Au NCs. In recent decades, both experimental and theoretical studies have demonstrated that these NCs have optimal catalytic properties, such as selective oxidation [12][13][14], selective hydrogenation [15][16][17][18], carbon-carbon coupling [19][20][21], photocatalytic [22], photoelectronic and photothermal reaction [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to the arrangement of surface ligands and metal atoms-as well as the electronic structure of the NC-may also affect the outcome of catalytic reactions, further convoluting structure-property relationships. 32 Indeed, differing trends have been reported for how NC size affects CO 2 RR activity. For example, in the series Au 25 (SR) 18 , Au 38 (SR) 24 , and Au 144 (SR) 60 (SR = SC 2 H 4 Ph), CO 2 RR activity increases with increasing NC size, 33 while other studies have found that the FE CO of Au-SR NCs is not directly affected by NC size.…”
Section: Introductionmentioning
confidence: 99%